2009
DOI: 10.1007/s11689-009-9008-9
|View full text |Cite
|
Sign up to set email alerts
|

Visuospatial working memory in children and adolescents with 22q11.2 deletion syndrome; an fMRI study

Abstract: 22q11.2 deletion syndrome (22q11DS) is a genetic disorder associated with a microdeletion of chromosome 22q11. In addition to high rates of neuropsychiatric disorders such as schizophrenia and attention deficit hyperactivity disorder, children with 22q11DS have a specific neuropsychological profile with particular deficits in visuospatial and working memory. However, the neurobiological substrate underlying these deficits is poorly understood. We investigated brain function during a visuospatial working memory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 69 publications
4
23
0
Order By: Relevance
“…The authors argued this to be related to the need to recruit more resources to perform the tasks. I another study, 22q11.2DS children and adolescents were compared to TD controls during a spatial working memory task (Azuma et al, 2009), researchers found a greater activation in the TD group in than children with 22q11DS in parietal and occipital regions with no significant difference in activation of frontal regions (dorso lateral prefrontal cortex) between both groups.…”
Section: Discussionmentioning
confidence: 99%
“…The authors argued this to be related to the need to recruit more resources to perform the tasks. I another study, 22q11.2DS children and adolescents were compared to TD controls during a spatial working memory task (Azuma et al, 2009), researchers found a greater activation in the TD group in than children with 22q11DS in parietal and occipital regions with no significant difference in activation of frontal regions (dorso lateral prefrontal cortex) between both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that children with 22q11.2DS tend to present significant decreased activation in the parietal and occipital lobe during a visuo-spatial working memory task (Azuma et al, 2009). From a clinical point of view, visuo-spatial impairments have been extensively reported in the syndrome (Wang et al, 2000, 2011; Simon et al, 2005a; Jacobson et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These studies have reported abnormal neural activity in tasks involving response inhibition (53) and working memory (54), specifically involving atypical parietal activation. Although differences in behavioral performance could contribute to the observed neurophysiologic differences, these findings offer preliminary evidence for atypical development of specific neural circuits critical for higher-order cognitive functions in 22q11DS.…”
Section: Endophenotypes In Mice and Menmentioning
confidence: 99%